Son los Gobiernos locales más eficientes cuando su coalición política está en el Gobierno central? Un estudio para el caso de las municipalidades en Chile; Are local governments more efficient as the same political coalition governs? A study among Chilean municipalities - José Martínez; César Salazar; Luis Améstica-Rivas (Estudios de Economía, 2020)
Últimamente, se ha generalizado una desconfianza en relación con la gestión de los recursos públicos. Este trabajo mide la eficiencia técnica de las municipali- dades en Chile, haciendo especial énfasis en aquellos factores de tipo político que inciden en la eficiencia en la gestión local. En particular, el foco es puesto en la relación entre la ideología política del Gobierno local con el Gobierno central. Para ello, se utilizan datos de panel de municipalidades chilenas para los a\~nos 2010-2016. Las estimaciones siguen dos etapas. Primero, se mide la eficiencia mediante el Análisis Envolvente de Datos. Segundo, se estima un modelo Probit Fraccional para explicar estos niveles. Las estimaciones se\~nalan que en promedio las municipalidades proveen un 49% menos de bienes y servicios que el óptimo. Niveles de eficiencia más altos se obtienen en comunas más grandes, urbanas y con mayor participación del Fondo Común Municipal. La eficiencia aumenta cuando el alcalde se presenta a reelección y se reduce en períodos en. – – Lately, questionings have emerged on how public resources are managed. This work calculates the technical efficiency of municipalities in Chile, with special emphasis on the political factors that drive efficiency in the management of local resources. In particular, focus is placed on the relationship between political ideology of the local government and central government. To do this, we use a panel data of Chilean municipalities for the years 2010-2016. The methodology follows two stages. First, we estimate efficiency scores by the Data Envelopment Analysis (DEA) approach. Second, a Fractional Probit model is estimated to explain these scores. The main results show that, on average, municipalities produce 49% achieve 49% less of output than the optimal. Higher levels of efficiency are obtained in larger, urban communes and with greater participation in the Municipal Common Fund. Efficiency increases when the mayor presents himself for a re-election and is reduced in the periods in which a left coalition governs. The later effect is reduced to the extent that the majority of the municipal council share the same ideology of the national government, suggesting an effect of the relationship between the central and local government on efficiency levels.
Keywords: D22; H72; C14; 330; Eficiencia; municipalidades; DEA; gestión; política; Efficiency; municipalities; DEA; management; politics